Analisis rute distribusi dengan jarak tempuh terpendek pada produk air mineral dalam kemasan (AMDK) (studi kasus CV. XYZ) - Bambang Herry Purnomo; Noer Noer Novijanto; Chandra Wahyu Ramadhan (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The local-brand mineral water industry faces intense market competition with the national mineral water industry. In order to be competitive, the local-brand mineral water industry must make various efficiency efforts to reduce production costs, including by planning short product distribution channels. CV. XYZ is a mineral water distributor company in Jember Regency which is also required to make efficient product distribution routes. The purpose of this research is to optimize to determine the shortest distribution route in order to save on the cost of distributing mineral water products. The method used is the Traveling Salesman Problem (TSP), namely the Nearest Neighbor and Cheapest Insertion Heuristic (CIH) methods. The two methods differ only in the exploration program, where Nearest Neighbor explores from any adjacent point, while CIH explores from a certain point and then traces through sub tours to find the shortest route. Based on the survey results, the distribution route currently covers the longest distance of 106.1 km. With the Nearest Neighbor method, the route can be shortened to 72.34 km with a distance saving percentage of 31.82% from the initial route. Meanwhile, the Cheapest Insertion Heuristic (CIH) method produces a total distance of 72.14 km with a distance saving percentage of 32.01%. Fuel savings with the first method of Rp. 1,043,184 while the second method is Rp. 1,049,376. These results indicate that the TSP method can help companies shorten time and save distribution costs.